Proceedings of the 20th ACM International Conference on Intelligent Virtual Agents 2020
DOI: 10.1145/3383652.3423875
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Cultural Tailoring of Virtual Agents

Abstract: Culturally informed design for virtual agents has been shown to positively impact health outcomes when tailored to target audiences. We present a participatory design methodology for culturally tailoring virtual agents. Investigators worked with key informants from our target population, members of predominantly Black church communities, to design culturally-relevant and sensitive virtual agent health promotion interventions. In the first participatory session, key informants designed agents to assist them wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…However, previous studies have suggested that a co-design process is required [63,64], and consideration of how user characteristics (eg, gender and ethnicity) and use context impact the perception of agent behaviors [43]. Moreover, specific agent features such as tailoring conversational agent characteristics to match user culture and personality [65,66], personalizing content [67], and expressing empathy [68] may boost rapport and engagement.…”
Section: Principal Findingsmentioning
confidence: 99%
“…However, previous studies have suggested that a co-design process is required [63,64], and consideration of how user characteristics (eg, gender and ethnicity) and use context impact the perception of agent behaviors [43]. Moreover, specific agent features such as tailoring conversational agent characteristics to match user culture and personality [65,66], personalizing content [67], and expressing empathy [68] may boost rapport and engagement.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Familiar clothing marker is explored to provoke a sense of familiarity with the conversational agent (Aljaroodi et al, 2020; O'Leary et al, 2020; Yadav et al, 2019; Murali et al, 2020; Lugrin et al, 2018. During a study, participants even considered that a certain dress was not considered appropriate (O'Leary et al, 2020). Similarly, in some contexts revealing clothes of avatars may be perceived as inappropriate (Aljaroodi et al, 2020).…”
Section: (23) Cultural Markersmentioning
confidence: 99%
“…Dickinson et al [28], for example, relied heavily on the network of street outreach workers managed by a partner organization to develop infrastructure for those workers to connect and collaborate. Some projects held research activities at common times and places of assembly for the community: e.g., regular meetings at a community center, alongside church services, or integrated with ceremonies [31,96,117,135,137]. In a few cases, researchers reported on significant efforts to reorient the traditional paradigm of HCI research and deconstruct design processes to give primacy to community knowledge practice [80,106,130].…”
Section: Enabling Participatory Models Formentioning
confidence: 99%
“…A minority of projects identified only outputs of the project for researchers (n=7, 15%). These projects often involved the development of design principles for a technological artifact or system immediately relevant for researchers, but not for the community [53,96,131].…”
Section: 23mentioning
confidence: 99%